DESIGN OF SHORT EVENING DRESS WITH PATTERN DESIGN TECHNIQUE FROM A HUNDRED COLORED LOINCLOTH, KANCHANABURI PROVINCE - Ampaikulwattsna, Nattamon; Ketwan, Kunathip; Rueangrot, Busakorn; Poupuree, Pornpimol; Sriwongsa, Supap (RMUTK Journal of Liberal Arts, 2022)
The research on the Design of Short Evening Dresses with Pattern Design Techniques from a Hundred Colored Loincloths from Kanchanaburi has two goals: 1) to design and make cocktail dresses with pattern techniques from a hundred coloured loincloths from Kanchanaburi, and 2) to study the satisfaction of the designed and made cocktail dresses with pattern techniques from a hundred coloured loincloth from Kanchanaburi. The target group was working women at Rat Burana District Office, Bangkok, for 52 people. The research tool is a questionnaire on satisfaction. The samples are selected with the purposive sampling technique. The data is analyzed for percentages, means, and standard deviations (SD). The findings point out that a hundred coloured loincloths have unique colours that show the local identity. Each fabric consists of a weft and a warp, creating a strange beauty. The filament is artificial thread, silky like artificial silk, with colours that have not faded, and is comfortable to wear. The loincloth is used for making cocktail dresses by using pattern techniques that have pleats and drapes in rhythms to make the designed dresses look extravagant and modern. The dresses designed with patterns and a hundred coloured loincloths of Kanchanaburi are in 10 sets. From the ten dresses, the experts in designing have selected five sets. I, the researcher, used the five dresses selected by the experts to make prototype dresses and survey the female samples’ satisfaction with the pattern design. The findings from the research show that the overall satisfaction for each dress shows that dresses 5, 3, 4, and 2 are satisfying at the highest level, respectively, with Dress 1 having the lowest mean. Concerning each aspect separately, for dresses 5, 3, 4 and 2, with the highest satisfaction levels, the samples focus on materials and dressmaking as the essential aspects, followed by the aspect of designing, with the aspect of a function having the lowest mean. As for Dress 1, the samples show that the most important parts are the materials and how the dress is made, followed by the function, and the design has the lowest mean.